Planar versus mesoscopic perovskite microstructures: The influence of CH3NH3PbI3 morphology on charge transport and recombination dynamics. (April 2016) - Pascoe, Alexander R.; Yang, Mengjin; Kopidakis, Nikos; Zhu, Kai; Reese, Matthew O.; Rumbles, Garry; Fekete, Monika; Duffy, Noel W.; Cheng, Yi-Bing
Abstract: Perovskite solar cells (PSCs) employing planar and mesoscopic architectures have both resulted in high efficiency devices. However, there is presently a limited understanding of the inherent advantages of both systems, particularly in terms of the charge transport and recombination dynamics. In the present study we characterize the relative benefits of the two most prominent CH3 NH3 PbI3 morphologies, primarily through time-resolved microwave conductivity (TRMC) and time-resolved photoluminescence (TRPL) measurements. The comparatively large perovskite grains, typical of planar assemblies, exhibited higher charge mobilities and slower trap-mediated recombination compared to the mesoscopic architectures. These findings reveal the injurious influence of grain boundaries on both charge transport and recombination kinetics, and suggest an innate advantage of planar morphologies. However, through impedance spectroscopy (IS) measurements, mesoscopic architectures were found to limit the interfacial recombination at the transparent conductive oxide (TCO) substrate. The lessons learnt through the characterization measurements were subsequently utilized to produce an optimized cell morphology, resulting in a maximum conversion efficiency of 16%. Graphical abstract: Highlights: Perovskite solar cells were characterized using transient and small-perturbation techniques. Large-grain planar morphologies present an inherent advantage over mesoscopic ones. The information derived from the characterization was used to optimize the cell structure.